2016
DOI: 10.1007/s00284-016-1145-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Lineages of Mycobacterium tuberculosis Isolates in Isfahan, Iran

Abstract: In this study, we aimed to identify the genetic lineages of Mycobacterium tuberculosis isolates in Isfahan via the mycobacterial interspersed repetitive-unit-variable number tandem repeat typing method based on 15 loci. Forty-nine M. tuberculosis isolates were collected between 2013 and 2015 from Tuberculosis patients in Mollahadi Sabzevari Tuberculosis Center in Isfahan. All isolates were typed by 15-locus MIRU-VNTR typing. The highest percentage of isolates, 44.89 % (22/49), belonged to the Euro-American lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In other studies conducted in Iran, the clustering ratio varied between 0.0 and 75%. The major reason for such discrepancies is the number of loci used; as the number of loci increases, the clustering ratio decreases due to the increased discriminatory power 17 , 19 , 34 , 35 , 48 , 49 . In our study, we established a high discriminatory power for MIRU-VNTR typing of 0.998 (HGDI).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other studies conducted in Iran, the clustering ratio varied between 0.0 and 75%. The major reason for such discrepancies is the number of loci used; as the number of loci increases, the clustering ratio decreases due to the increased discriminatory power 17 , 19 , 34 , 35 , 48 , 49 . In our study, we established a high discriminatory power for MIRU-VNTR typing of 0.998 (HGDI).…”
Section: Discussionmentioning
confidence: 99%
“…There have been three previous studies regarding the circulation of Beijing genotype in Iran, ranging from 1.7 to 24%. Additionally, this genotype has been located in the northern neighboring countries of Iran, including Kazakhstan, Georgia, Russia, as well as countries in Central and East Asia [34][35][36][37][38][39][40][41] . This indicates that the Beijing genotype is spreading across the region, and highlights the importance of further research into its circulation and how it can be better managed.…”
Section: Discussionmentioning
confidence: 99%
“…For example, of the total isolates surveyed recently, 59.1% in northern India (Sharma et al 2017 ), 53.4% in Pakistan (Bakuła et al 2019 ), and 41.8% in Iraq (Ahmed et al 2014 ) belonged to the Delhi/CAS sub-lineage. In reviewing the articles, we did not find an independent study from Afghanistan, but Delhi/CAS was the most prevalent (36.4%) sub-lineage among Afghan refugee patients living in Iran (Riyahi Zaniani et al 2017 ). The Delhi/CAS prevalence varies in different parts of Iran, although it seems to be more common in the central provinces.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, low clustering rates, 2 % and 2.6 %, were observed in two previous studies from Ecuador [69, 70] respectively. Another Iranian study [71] reported that the clustering rate of the 15-locus MIRU-VNTR was 0.0 (0 %). On the other hand, a Ghanaian study [72] estimated a high clustering rate of 41.2 %, which indicates high recent TB transmission and subsequent occurrence of unsuspected outbreaks in Ghana.…”
Section: Discussionmentioning
confidence: 99%